‘Colections’ by an English Nun in Exile: Bibliothèque Mazarine 1202. Edited by Julia Bolton Holloway - Gribbin, Anselm J. (The journal of theological studies, 2007)
This volume of the Analecta Cartusiana is a transcription of Paris, Bibliothèque Mazarine MS 1202. The manuscript, dated 23 July 1724 , was written anonymously by an English Benedictine nun in exile, and is an anthology of contemplative writings. Included in these ‘Colections’ are several writings of Dom Augustine Baker, Angela of Foligno, Bishop Fénelon of Cambrai's Letters of Spiritual Direction, and extracts from Dame Gertrude More's and Dame Catherine Gascoigne's defence of Baker's writings, sent to the General Chapter of the English Benedictine Congregation in 1633. The anonymous scribe, identified as Sister Mary Benedicte Dally, also included a collection of near-quotations from Julian of Norwich's Showings.